Economic recession and mental health distress among Japanese people in middle age - Hiroshi Murayama; Yukitsugu Komazawa; Masako Kakizaki; Yoshiharu Fukuda; Takahiro Tabuchi (Scientific Reports)
Abstract This study examined the association between the 2008 economic recession and mental health distress among middle-aged Japanese people, and whether sex and socioeconomic status affected this association. Data were obtained from a nationwide longitudinal study (“Longitudinal Survey of Middle-aged and Elderly Persons”), conducted since 2005 on randomly selected Japanese adults aged 50–59 years. Of the 34,240 respondents to the 2005 baseline survey, data for 33,815 who responded at least once both before 2007 and after 2008 were analyzed. The 6-item Kessler Psychological Distress Scale (K6) was used to assess mental health distress (i.e., K6 scores of ≥ 5). A generalized estimating equation model applied to 6 years of longitudinal data (2005–2010) showed that mental health worsened among men and women after the 2008 recession (odds ratio [95% confidence interval] = 1.11 [1.07–1.15] for men; 1.14 [1.10–1.18] for women), particularly among self-employed men (1.08 [1.02–1.14]). The mental health of women who graduated from junior high school worsened less than that of women who graduated from university or graduate school (0.89 [0.80–0.98]). This study confirmed the association between the 2008 economic recession and mental health distress and identified vulnerable socioeconomic groups. These findings provide useful information for future economic crises.